A Dynamic Programming Algorithm for the Fused Lasso and L 0-Segmentation - Johnson, Nicholas A. (Journal of computational and graphical statistics, 2013)
We propose a dynamic programming algorithm for the one-dimensional Fused Lasso Signal Approximator (FLSA). The proposed algorithm has a linear running time in the worst case. A similar approach is developed for the task of least squares segmentation, and simulations indicate substantial performance improvement over existing algorithms. Examples of R and C implementations are provided in the online Supplementary materials, posted on the journal web site.